2015
DOI: 10.3389/fpubh.2015.00006
|View full text |Cite
|
Sign up to set email alerts
|

Health Care Providers and Human Trafficking: What do They Know, What do They Need to Know? Findings from the Middle East, the Caribbean, and Central America

Abstract: Background: Human trafficking is a crime that commonly results in acute and chronic physical and psychological harm. To foster more informed health sector responses to human trafficking, training sessions for health care providers were developed and pilot-tested in the Middle East, Central America, and the Caribbean. This study presents the results of an investigation into what health care providers knew and needed to know about human trafficking as part of that training program.Methods: Participants attended … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
45
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 18 publications
1
45
0
Order By: Relevance
“…The authors are grateful for support from safeguarding leads and trainers across the 10 Contributors SO, CZ and LMH conceived the study and developed the PROTECT questionnaire. SO oversaw data collection.…”
Section: Acknowledgementsmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors are grateful for support from safeguarding leads and trainers across the 10 Contributors SO, CZ and LMH conceived the study and developed the PROTECT questionnaire. SO oversaw data collection.…”
Section: Acknowledgementsmentioning
confidence: 99%
“…A pretraining survey of 178 healthcare professionals attending human trafficking training in the Middle East, Caribbean and Central America reported generally high levels of knowledge regarding the health outcomes associated with human trafficking, but found that many healthcare professionals lacked awareness of their role in responding to victims of human trafficking. 10 In the UK, a qualitative study of seven healthcare professionals working with female victims of trafficking for sexual exploitation found that staff reported difficulties with building trusting relationships with trafficked patients and with coping with the emotional burden of women's needs and experiences. 11 To the best of our knowledge, no previous research has investigated whether UK health professionals come into contact with victims of human trafficking, their knowledge and readiness to respond to human trafficking, or their training needs.…”
Section: Introductionmentioning
confidence: 99%
“…Access to timely, high‐quality healthcare is integral to trafficked people's recovery (Baldwin, Eisenman, Sayles, Ryan, & Chuang, ). Healthcare providers can play a critical role in identifying victims of trafficking and making referrals for further support (Viergever, West, Borland, & Zimmerman, ). Yet many victims encounter difficulties accessing appropriate healthcare both during the time they are exploited and after their escape (Westwood et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Research conducted in the USA similarly found that trafficked people who were able to access healthcare during the time they were being exploited were unable to disclose their experiences of abuse because of language barriers and limited opportunities to speak privately with healthcare professionals (Baldwin et al, ). Survey research conducted with healthcare professionals in various settings suggests that many healthcare providers lack the requisite knowledge and confidence to identify and respond appropriately to patients they suspect may have been trafficked (Ross et al, ; Viergever et al, ). Yet, despite the need for improved health service responses, there is limited evidence from providers about the challenges related to meeting the needs of trafficked people.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation